USING IDOL MODEL TO DEVELOP WRITING FOR ACADEMIC PURPOSES INSTRUCTIONAL BLOCKS FOR THE FIFTH SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT UIN ALAUDDIN MAKASSAR - Ummu Rofikah (Universitas islam Negeri Alauddin Makassar, 2019)
This study is a development research aiming to develop a prototype of writing for academic purposes instructional block using IDOL model for the fifth semester students of English Education Department at UIN Alauddin Makassar. IDOL (Input, Development, Output, Language Acquisition) model was implemented as material development model. The study involved 101 respondents i.e. 87 students, 10 graduates, and 4 lecturers from English Education Department at UIN Alauddin Makassar. The research instruments employed were need analysis questionnaire and interview guidelines for students, graduates, and lecturers. While the quantitative data were analyzed using frequency analysis, the qualitative data were analyzed using data condensation, data display, and conclusion drawing. The study results revealed the students’ subjective and objective needs in the material of writing for academic purposes which subsequently became the basis of the writing for the syllabus design. Ultimately, a unit of prototype demonstrating the development of instructional block development using IDOL model was developed as an output of this study. This research can be a helpful guideline in developing a teaching material by using IDOL model, and the designed syllabus can be used in teaching writing for academic purposes since the syllabus had been sequenced and graded carefully by considering students’ needs and lecturer’s suggestions.